2017
DOI: 10.1183/13993003.02467-2016
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insight into the function of the microbiome in lung diseases

Abstract: The lung harbours a diverse array of microbes whose dynamic composition is influenced by both host and environmental factors. Thus far, most studies have described the microbial composition of healthy or diseased lungs and provided an overview of the differences between topographical locations within the respiratory tract. However, insight into the functional mechanisms underlying host-microbe interactions and how they might drive lung health and disease are limited. This review provides an overview of the cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
69
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 96 publications
(132 reference statements)
2
69
0
3
Order By: Relevance
“…Many studies on the gut have reported changes to the immune phenotype, with deficits of both the innate and adaptive immune components of the intestinal mucosa in GF mice. Several bacterial species have been shown to have different modulatory effects on the host immune system, highlighting the need for specific bacteria within a given developmental window for the normal patterning of host immunity ( Olszak et al, 2012 ; Ubags and Marsland, 2017 ). GF mice have a thinner lamina propria, with fewer resident mature immune cells, and the presence of a complex microbiota triggers the proliferation, differentiation, and maturation of immune cells, leading to an increase in microbiota-selected IgA + (immunoglobulin A) plasma cells or T-cell subsets, such as T reg Foxp3, Th1 (T-helper), Th2, and Th17 lymphocytes ( Macpherson and Uhr, 2004 ; Gaboriau-Routhiau et al, 2009 ; Ivanov et al, 2009 ).…”
Section: Impact Of the Lung Microbiota On The Adaptive And Innate Immmentioning
confidence: 99%
“…Many studies on the gut have reported changes to the immune phenotype, with deficits of both the innate and adaptive immune components of the intestinal mucosa in GF mice. Several bacterial species have been shown to have different modulatory effects on the host immune system, highlighting the need for specific bacteria within a given developmental window for the normal patterning of host immunity ( Olszak et al, 2012 ; Ubags and Marsland, 2017 ). GF mice have a thinner lamina propria, with fewer resident mature immune cells, and the presence of a complex microbiota triggers the proliferation, differentiation, and maturation of immune cells, leading to an increase in microbiota-selected IgA + (immunoglobulin A) plasma cells or T-cell subsets, such as T reg Foxp3, Th1 (T-helper), Th2, and Th17 lymphocytes ( Macpherson and Uhr, 2004 ; Gaboriau-Routhiau et al, 2009 ; Ivanov et al, 2009 ).…”
Section: Impact Of the Lung Microbiota On The Adaptive And Innate Immmentioning
confidence: 99%
“…Most of the recent advances in microbial ecology have been made possible thanks to the development of next-generation sequencing technologies which allow the analysis of complex microbial populations in different body niches, including the respiratory tract. Multiple studies of the human-associated microbiota have suggested a fundamental role of microbes, and predominantly bacteria, in maintaining health and a role for changes in lung microbiota in contributing to diseases such as chronic obstructive pulmonary disease (COPD), bronchiectasis and cystic fibrosis (CF) [ 2 , 3 , 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gut dysbiosis can induce colonic inflammation and bacterial translocation, which accelerate the progression of NAFLD . Lung dysbiosis is associated with lung function . Recently, an interchange between gut and lung microbiota has been noted, suggesting that changes in one compartment could affect the microbial composition and function in the other compartment …”
Section: Discussionmentioning
confidence: 99%